1997
DOI: 10.1016/s0893-133x(97)00022-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of YM-43611, a Novel Dopamine D2-Like Receptor Antagonist, on Immediate Early Gene Expression in the Rat Forebrain

Abstract: The pharmacological characteristics of two benzamides, YM-43611, a potent and selective dopamine D 3 and D 4 antagonist, and YM-09151-2 (nemonapride), were compared with two reference antipsychotic agents, haloperidol and clozapine, in terms of modification of c-fos and related gene expression in the rat forebrain. After subcutaneous injection of YM-43611 (1 or 5 mg/kg), nemonapride (4 mg/kg), haloperidol (1 mg/kg), or clozapine (25 mg/kg), Fos immunocytochemistry was employed, and the distributions of Fos-lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…3a), whereas haloperidol (0.04 mg/kg) and L-741626 (2.5 mg/kg) both failed to cause significant changes in Fos-LI. Previous reports examining the effects of haloperidol concur with our findings (Hurley et al, 1996;Kovacs et al, 2001;Kurokawa et al, 1997); however one study using a higher dose found a small but significant increase after haloperidol treatment (Vahid-Ansari and Robertson, 1996). The robust increase in ICjM Fos-LI observed after treatment with SB-277011-A (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…3a), whereas haloperidol (0.04 mg/kg) and L-741626 (2.5 mg/kg) both failed to cause significant changes in Fos-LI. Previous reports examining the effects of haloperidol concur with our findings (Hurley et al, 1996;Kovacs et al, 2001;Kurokawa et al, 1997); however one study using a higher dose found a small but significant increase after haloperidol treatment (Vahid-Ansari and Robertson, 1996). The robust increase in ICjM Fos-LI observed after treatment with SB-277011-A (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…The mechanisms underlying this action, although investigated intensively, remain to be established. Recent studies involving the Fos protein have demonstrated that clozapine induces a much larger increase in the number of neurons that exhibit Fos-like immunoreactivity (LI) in the medial prefrontal cortex (mPFC) than do typical neuroleptics (Deutch and Duman 1996; Fink-Jensen and Kristensen 1994; Fink-Jensen et al 1995;Guo et al 1995;Kurokawa et al 1997;Robertson and Fibiger 1992;Robertson et al 1994;Wan et al 1995). This regionally specific clozapine effect sets it apart from typical neuroleptics.…”
mentioning
confidence: 99%